Impacto de la participación ciudadana en la toma de decisiones del gobierno autónomo descentralizado el empalme, 2023. - Villegas Castro, Gema Milena (2025)
This research project focuses on the “Impact of Citizen Participation in Decision Making in the Decentralized Autonomous Government of Canton El Empalme”. The research aims to evaluate the impact of citizen participation in decision-making in this Decentralized Autonomous Government during the year 2023, using descriptive, exploratory and correlational research approaches. Although through different forms of communication, the data reveal that public engagement remains exceedingly minimal, a considerable proportion of the population remains uninformed about the means of their participation, evidenced by the high proportion of citizens who are unaware of the available participation mechanisms. This situation underscores the urgent need to improve the dissemination and accessibility of such mechanisms. Efforts to strengthen citizen participation have faced significant challenges, such as incorrect data collection, doubts about the effectiveness of procedures, and resource constraints. Citizen participation requires a strong commitment to these challenges. Research indicates that improving transparency within social networking platforms and promoting spaces for dialogue can improve civic engagement. The evaluation of citizen participation in local actions in 2023 shows that improvements are needed in certain aspects to improve municipal administration and growth, although 73% of citizens consider that these actions gain legitimacy and effectiveness from their participation.